Sexual dysfunction in women with breast cancer: a forgotten aspect among survivors - Adele Isanazar; Zahra Akhlaghi; Fatemeh Nejatifar; Nastaran Mirfarhadi (BMC Women's Health)
Abstract Introduction Breast cancer strongly affects sexual desires physical and sexual attractiveness. This study was conducted to assess sexual function and related factors among women with breast cancer. Materials and methods This study was performed on 149 women with breast cancer diagnosed by an oncologist, and the demographic and clinical data were also recorded. The Female Sexual Function Index (FSFI) was used to assess sexual function in women. Results The mean score of sexual function in patients was 16.44 ± 8.85. Among participants, 137 (91.9%) had sexual dysfunction. The most frequent sexual disorder was related to dissatisfaction (75.8%) and arousal problems (72.5%). All disorders of sexual functions were significantly higher among patients older than 51 years, with pre-high school education level, menopausal status, marriage duration 28.40 ± 9.46years, number of children ≥ 3, and duration of breast cancer more than seven months (p < 0.05). The frequency of all sexual disorders, except for sexual function, was significantly higher in patients diagnosed with stage III breast cancer (p < 0.05). The complications in vaginal lubrication, and orgasm was significantly higher in those who underwent radiation therapy (p < 0.05). The results of this logistic regression analysis indicate that age and the duration of breast cancer are significantly associated with the likelihood of sexual dysfunction in the women (p < 0.05). Conclusion This study reveals a high prevalence of sexual dysfunction among women with breast cancer, with a notably low mean sexual function score. Key factors contributing to these challenges include age, education level, menopausal status, and the duration of both breast cancer and marriage.